Accounting for performance variation: How important are intangible resources? - Galbreath, Jeremy; Galvin, Peter (Curtin University of Technology, 2006)
The primary mission of strategic management research is to explain variations in the performance of firms. As researchers have sought to explain differentials in firm performance, they have looked to the factors that underlie competitive advantage. For many years, industry structure factors were considered the key factors of interest although recently, the resource-based view of the firm (RBV) has taken center stage and posits that firm resources ? namely intangible resources ? rather than structural factors, are the underlying source of competitive advantage. However, this study demonstrates that research studies that have expressly set out to investigate intangible resources contain clear deficiencies. In an effort to overcome these deficiencies, theoretical and methodological improvements are developed to study intangible resources ? and to verify the RBV. Through studying 291 firms, the results indicate that intangible resources are important factors in explaining variations in firm performance, even after accounting for the effects of tangible resources and industry structure factors. Interestingly, our finding with respect to capabilities suggests that this intangible resource might not be the ?ultimate? source of sustainable competitive advantage, contrary to theory.